Sistem Manajemen Keselamatan dan Kesehatan Kerja Di Perseroan Terbatas Nilam Sari Cipta Amrizal - Syarifa Mahila; Nazifah Nazifah; Upik Ema Emilia Susanti (Universitas Batanghari Jambi, 2020)
Limited Liability Company, Nilam Sari Cipta Amrizal, is a company engaged in the Electrical Contracting sector based in Jambi. Based on the type of business activity, this company has a high risk to Occupational Health & Safety. The purpose of this study was to determine the application of the Occupational Safety and Health Management System in the Limited Liability Company of Nilam Sari Cipta Amrizal, the obstacles faced and the efforts to solve them. Occupational health and safety is one of the workers' rights that must be fulfilled as regulated in Government Regulation Number 50 Year 2012. The research method used is a juridical empirical research type with an analytical approach. In this study, the authors describe the problems under study, which are arranged based on theory and related concepts to obtain a comprehensive and systematic description of the occupational safety and health management system, data sources from field research using interview methods and literature research. Data obtained from field research and library research are processed using qualitative analysis, namely data analysis based on what is obtained from the field and literature both orally and in writing, presented in the form of logical sentences. The method used is the inductive thinking method, namely the method of thinking. from a specific nature then drawn to a general conclusion.